Generation, Development and Modifications of Natural Fibers - Abbas, Mudassar; Jeon, Han-Yong (IntechOpen, 2020)
This book covers natural fibers at the basic level as well as a few advanced approaches for recent trends in natural fibers. The core chapters include an introduction to cellulosic fibers like cotton, protein fibers like silk, and other natural fibers. Overall the book provides comprehensive knowledge of natural fibers.